2012
DOI: 10.1016/j.ypmed.2012.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Parent awareness of young children's physical activity

Abstract: Objective Parents who overestimate their child’s physical activity (PA) level may not encourage their children to increase their PA. We assessed parental awareness of child PA, and investigated potential correlates of overestimation. Method Child PA (accelerometer) and parent-classified child PA [‘active’ ≥ 60mins/day vs. ‘inactive’ <60mins/day moderate and vigorous PA (MVPA)] were measured over 7 days [n=329, 44% male, 39% Latino; Mean (SD) 9.1 (0.7) yrs] in an obesity prevention study in San Diego (Project… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 23 publications
4
50
1
Order By: Relevance
“…8 No impact on ST was observed, and at postassessment, mean measured minutes were 25% above that reported by Mathews et al 17 in 2008. As identified in the literature, strategies to minimize ST while promoting PA in youth are important for childhood obesity prevention programs.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…8 No impact on ST was observed, and at postassessment, mean measured minutes were 25% above that reported by Mathews et al 17 in 2008. As identified in the literature, strategies to minimize ST while promoting PA in youth are important for childhood obesity prevention programs.…”
Section: Discussionmentioning
confidence: 50%
“…7 In 2008, only 42% of US children, 6 to 11 years of age, engaged in the recommended 60 minutes per day of MVPA. 8 In addition, researchers have found that children, 6 to 15 years of age, spend an average of 5 to 7 hours (300-420 minutes) per day in sedentary behaviors and that the sedentary lifestyle of parents is a contributing factor in the childhood obesity epidemic. 9 Strategies to minimize sedentary time (ST) while promoting PA in youth should be a focus in obesity prevention programs.…”
Section: Topics In Clinical Nutrition/april-june 2015mentioning
confidence: 99%
“…For example, Hinkley and colleagues [290] report that different factors influence preschool boys’ and girls’ participation in physical activity. It also appears that parents often overestimate the amount of activity that their children get [291]. Therefore, objective assessment of physical activity in children is important.…”
Section: Figurementioning
confidence: 99%
“…72 Parent-reported barriers to increasing preschooler PA include lack of knowledge about what constitutes MVPA, difficulty measuring daily activity, outdoor safety, inability to monitor or engage in PA with their child, parent dislike of PA, and inclement weather. 73,74 Caregivers may overestimate the amount of PA their preschoolers are getting at (pre)school or daycare, 75 which may further hinder encouraging PA at home. While homes of obese preschoolers have been found to have fewer PA devices, 76,77 studies have not consistently found preschoolers with overweight or obese engage in lower levels of PA than their healthy weight peers.…”
Section: Reach Of Preschool Weight Control Trialsmentioning
confidence: 99%